Diagnosis in France of a Non-Toxigenic tox Gene-Bearing Strain of Corynebacterium diphtheriae in a Young Male Back From Senegal. (9th January 2017) - Billard-Pomares, Typhaine; Rouyer, Cécile; Walewski, Violaine; Badell-Ocando, Edgar; Dumas, Marc; Zumelzu, Coralie; Jaureguy, Françoise; Brisse, Sylvain; Caux, Frédéric; Bouchaud, Olivier; Carbonnelle, Etienne
Abstract: Cutaneous diphtheria is uncommon in Europe. In this study, we report a case of imported cutaneous infection due to a non-toxigenic but tox gene-bearing (NTTB) strain of Corynebacterium diphtheriae . The NTTB strains are recognized as emerging pathogens across Europe, and physicians and bacteriologists should be aware of the circulation of these strains.